Kinerja Pegawai dalam Meningkatkan Pelayanan Administrasi Kependudukan di Dinas Kependudukan dan Catatan Sipil Kota Manado. - Marbun, Susanti; Posumah, Johnny Hanny; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Background: The low quality of public services is happening lately is one beam that is directed at the government in providing services to the public. This is evident from the number of complaints from the public, both directly and through the mass media, such as a convoluted procedure, there is no certainty of completion period, costs, requirements that are not transparent, the attitude of officers who are less responsive, etc; giving rise to unfavorable image of the government. Like most of the case, that the level of ease of service, especially for the middle to the bottom is still very low. One of the services that the public is often complained of population administration services. So authors interested in studying how to Improve Employee Performance Services Population Administration in the Department of Population and Civil Registration Manado City. Research Methodology: This study used qualitative research methods through direct observation, interviews with 17 informants related, and documentation assisted with additional instruments such as interview, recording devices, and stationery. Results: Based on performance indicators, namely Productivity, Accountability, Quality of Service, Responsiveness and Responsibility then get the results that Employee Performance in Improving Population Administration Service in the Department of Population and Civil Registration Manado City is quite good, although there are some constraints such as infrastructure which needs to be was added, and the lack of information about the requirements in the management of civil documents. Conclusion: Employee Performance in Improving the Population Administration Services in the Department of Population and Civil Registration Manado based on research that has been done can be said is good enough.Key Word : Employee Performance in Improving the Population Administration Servic